Mapping the Transformation of Educational Management through Artificial Intelligence: A PRISMA-Based Systematic Review - Slaitan, Fettouma (Eximia, 2025)
Despite the exponential interest of researchers and policymakers over the past two decades in integrating AI into education, there is a clear lack of comprehensive studies on AI in the context of educational management and governance, given that most research in this area is focused on educational leadership. To this end, this article presents a systematic review of the literature conducted according to the PRISMA protocol in order to explore the state of the art of research on the role of AI as a lever for transforming education management for the period 2000-2025. It draws on an academic corpus of research and studies indexed in the Scopus and Web of Science databases. The present work sheds light on key diilensions IA is redefining , namely governance , stategic and operational management.. The results reveal that AI acts as a decision-making tool, a means of optimizing administrative processes, and a strategic management instrument, while raising major challenges related to algorithmic governance, equity, and institutional accountability. Five major transformative dimensions of educational management are highlighted in this study: redefining educational performance, streamlining internal processes, skills management and organizational learning, data and systems governance, and decision-making driven by predictive analytics.